Time‐resolved identification of mechanical loadings on plates using the virtual fields method and deflectometry measurements. (12th December 2017) - O'Donoughue, P.; Robin, O.; Berry, A.
Abstract: This paper describes an approach for identifying the magnitude and location of both stationary and transient mechanical loadings applied to a thin rectangular simply supported plate. Full‐field deflectometry measurements and the virtual fields method are used with the local equilibrium equation of the plate in the time domain to solve the force reconstruction problem, whereas previous work by the authors used this last equation in the frequency domain. As a result, it is possible to reconstruct load time history in addition to magnitude and location. Experimental results of this complete identification are presented for two different instrumented mechanical exciters: electrodynamic shaker and impact hammer for stationary and transient excitations, respectively. The approach is then applied to determine the location and time of multiple unknown transient excitations produced by a set of impacting metal marbles.